2020
DOI: 10.21577/0103-5053.20200069
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Multi-Element Composition and Biological Activities of Extracts and Lupenone from Albizia inundata (Mart.) Barneby & J.W.Grimes

Abstract: In this study, antimicrobial activity of extracts and lupenone from A. inundata (Fabaceae, Mimosoideae), were tested. In addition, the multi-element composition of the leaves, bark and stems (heartwood) of A. inundata was evaluated using inductively coupled plasma optical emission spectrometry (ICP OES). Lupenone was isolated in the petroleum ether extract of leaves, for the first time. Biological assays were conducted to evaluate the antimicrobial (antibacterial, antifungal and antiparasitic) of extracts, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Lupenone was earlier identified in ethyl acetate extract of A. coriaria stem bark (Byamukama et al 2015). It was also isolated from petroleum ether leaf extract of Albizia inundata (Andrade et al 2020) as well as stem bark extracts of Albizia julibrissin (Baek et al 2010), Albizia gummifera (Rukunga and Waterman 2001a), Albizia versicolor, Albizia schimperana (Rukunga and Waterman 2001b) and Albizia falcataria (Arifnuryadin and Affandi 1998). Lupenone is a lupane-type triterpenoid with appreciable antioxidant activity (Çulhaoğlu et al 2015;Jeong et al 2013) and antibacterial activity against E. coli, S. aureus, P. aeruginosa and Bacillus subtilis (Prachayasittikul et al 2010).…”
Section: Compounds Identified In Fractions Of a Coriaria Leaves Extractmentioning
confidence: 97%
“…Lupenone was earlier identified in ethyl acetate extract of A. coriaria stem bark (Byamukama et al 2015). It was also isolated from petroleum ether leaf extract of Albizia inundata (Andrade et al 2020) as well as stem bark extracts of Albizia julibrissin (Baek et al 2010), Albizia gummifera (Rukunga and Waterman 2001a), Albizia versicolor, Albizia schimperana (Rukunga and Waterman 2001b) and Albizia falcataria (Arifnuryadin and Affandi 1998). Lupenone is a lupane-type triterpenoid with appreciable antioxidant activity (Çulhaoğlu et al 2015;Jeong et al 2013) and antibacterial activity against E. coli, S. aureus, P. aeruginosa and Bacillus subtilis (Prachayasittikul et al 2010).…”
Section: Compounds Identified In Fractions Of a Coriaria Leaves Extractmentioning
confidence: 97%
“…These results correlate with the findings of Nigussie et al [ 52 ], who showed that Albizia gummifera (family Fabaceae) aqueous and n-butanol extracts inhibited the growth of L. donovani amastigote. On the other hand, Andrade et al [ 53 ] did not find anti-leishmanial potential in Albizia inundata (family Fabaceae) extracts. The difference in antiparasitic activity may be due to the differences in plant species and the extraction solvents associated with the biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…The LC-MS analysis of the methanolic extract from O. baccatus branches identified 13 major compounds, and some of them are thought to be responsible for the extract’s antibacterial and anticancer activities ( Table 3 ). Maslinic acid (RT 7.23 min), oleanolic acid (RT 8.44 min) and its derivatives, and lupenone (RT 16.06 min) have been found to possess antibacterial and anticancer activities [ 20 , 21 , 22 , 23 , 24 , 25 ]. β-amyrin (RT 7.23 min) and phytanic acid (RT 15.14 min) have also been found to demonstrate anticancer activity [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%